Question
upstudy study bank question image url

(71) \( \log x=1-\log (x-3) \)

Ask by Daniel Potter. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x = 5 \)

Solution

We start with the equation:   log x = 1 - log(x - 3) Step 1. Add log(x - 3) to both sides to combine logarithms:   log x + log(x - 3) = 1 Step 2. Use the product rule of logarithms:   log [x(x - 3)] = 1 Step 3. Rewrite the equation in exponential form. Assuming the logarithm is base 10, we have:   x(x - 3) = 10¹ = 10 Step 4. Expand and rearrange the equation:   x² - 3x - 10 = 0 Step 5. Factor the quadratic equation:   (x - 5)(x + 2) = 0 Step 6. Solve each factor:   x - 5 = 0 ⟹ x = 5   x + 2 = 0 ⟹ x = -2 Step 7. Check the domain of the logarithms:   For log x: x > 0   For log(x - 3): x - 3 > 0 ⟹ x > 3 Thus, x must be greater than 3. The solution x = -2 does not satisfy this. Final Answer: x = 5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( \log x = 1 - \log (x-3) \), we can use the properties of logarithms. First, we can rewrite it as: \[ \log x + \log (x-3) = 1. \] Using the property that \( \log a + \log b = \log(ab) \), we have: \[ \log(x(x-3)) = 1. \] This implies: \[ x(x-3) = 10^1 = 10. \] Expanding the left-hand side gives us: \[ x^2 - 3x - 10 = 0. \] Now, we can solve this quadratic equation using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{3 \pm \sqrt{(-3)^2 - 4 \cdot 1 \cdot (-10)}}{2 \cdot 1} = \frac{3 \pm \sqrt{9 + 40}}{2} = \frac{3 \pm \sqrt{49}}{2}. \] This simplifies to: \[ x = \frac{3 \pm 7}{2}. \] Calculating the two possible values, we find: \[ x = \frac{10}{2} = 5 \quad \text{and} \quad x = \frac{-4}{2} = -2. \] However, since the logarithm is only defined for positive values, we discard \( x = -2 \). Therefore, the solution to the equation is: \[ \boxed{5}. \] It's always important to check that the solution we found satisfies the original logarithmic equations! For \( x = 5 \): \(\log(5) = 1 - \log(2)\) simplifies correctly, confirming that \( x = 5 \) is indeed valid.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy